N8‐acetylspermidine as a potential plasma biomarker for Snyder‐Robinson syndrome identified by clinical metabolomics. Issue 1 (15th July 2015) - Abela, Lucia; Simmons, Luke; Steindl, Katharina; Schmitt, Bernhard; Mastrangelo, Massimo; Joset, Pascal; Papuc, Mihaela; Sticht, Heinrich; Baumer, Alessandra; Crowther, Lisa M.; Mathis, Déborah; Rauch, Anita; et al.
Abstract: Clinical metabolomics has emerged as a powerful tool to study human metabolism in health and disease. Comparative statistical analysis of untargeted metabolic profiles can reveal perturbations of metabolite levels in diseases and thus has the potential to identify novel biomarkers. Here we have applied a simultaneous genetic‐metabolomic approach in twin boys with epileptic encephalopathy of unclear etiology. Clinical exome sequencing identified a novel missense mutation in the spermine synthase gene ( SMS ) that causes Snyder‐Robinson syndrome (SRS). Untargeted plasma metabolome analysis revealed significantly elevated levels of N 8 ‐acetylspermidine, a precursor derivative of spermine biosynthesis, as a potential novel plasma biomarker for SRS. This result was verified in a third patient with genetically confirmed SRS. This study illustrates the potential of metabolomics as a translational technique to support exome data on a functional and clinical level.